Geochemistry of komatiites from the Tipasjärvi, Kuhmo, Suomussalmi, Ilomantsi and Tulppio greenstone belts, Finland: implications for tectonic setting and Ni sulphide prospectivity - Maier, Wolfgang D.; Peltonen, P.; Halkoaho, T.; Hanski, E. (Precambrian Research, 2013)
Komatiites and komatiitic basalts within the Neo-Mesoarchaean, ca. 2.8 Ga greenstone belts in the western part of the Karelian craton in Finland formed in diverse palaeoenvironments. The lavas in the Tipasjärvi and Kuhmo greenstone belts formed in an oceanic plateau environment, whereas the komatiites of the Suomussalmi belt formed in a continental rift setting, consistent with Nd and Pb isotope data of Suomussalmi felsic volcanics indicating the presence of older (>3 Ga) crust in the belt. The komatiites and komatiitic basalts of the Ilomantsi greenstone belt show trace element systematics similar to those of modern continental arc volcanics, implying interaction of the lavas with felsic arc volcanics. PGE contents are low (2–4 ppb Pt and Pd each) relative to most other Al-undepleted komatiites from elsewhere, interpreted to result from equilibration with sulphides during emplacement. Xenocrystic zircon grains, up to 3.2 Ga in age, in some felsic volcanics and granitoids that are coeval with the komatiites indicate the presence of older continental basement in the Ilomantsi area. The Ilomantsi komatiites are interpreted to have formed at an active continental margin where basement rocks were extensively intruded and assimilated by felsic plutonic massifs. The komatiites of the Tulppio belt in northern Lapland resemble those of the Tipasjärvi, Kuhmo and Suomussalmi belts, but due to limited data, their emplacement environment remains uncertain. The Ni sulphide prospectivity of the Finnish komatiite belts appears to be relatively low, despite the identification of geochemical signatures of PGE depletion and crustal contamination in the Ilomantsi belt and, to a lesser degree, Suomussalmi and Tulppio belts, the presence of locally sulphide-bearing felsic volcanics and sedimentary rocks in the footwall of some of the komatiites, and the discovery of several small magmatic sulphide deposits in the Kuhmo, Suomussalmi, Ilomantsi and Tulppio belts. The main reasons are that the Finnish komatiites are relatively ...